Gram‐Typing Using Conjugated Oligoelectrolytes. (19th August 2020) - Zhou, Cheng; Ho, James C. S.; Chia, Geraldine W. N.; Moreland, Alex S.; Ruan, Lin; Liedberg, Bo; Kjelleberg, Staffan; Hinks, Jamie; Bazan, Guillermo C.
Abstract: It is shown that Gram‐type differentiation, an essential tool in microbiology, can now be easily accomplished by using the chain‐elongated conjugated oligoelectrolyte COE‐S6 . Specifically, COE‐S6 can be used as a fluorescent membrane probe that distinguishes between Gram‐negative and Gram‐positive bacteria in a single step. Confocal microscopy of labeled microorganisms and differential scanning calorimetry with phospholipid‐ and lipopolysaccharide‐containing model membranes suggest that lipopolysaccharides impede COE‐S6 membrane intercalation in Gram‐negative bacteria. Both Gram‐types within a mixture are discretely labeled by counterstaining COE‐S6 with the nonspecific and lipophilic membrane probe FM 4–64 . This single‐step procedure allows for the in situ visualization of individual Gram‐types in complex polymicrobial biofilms. Given that COE‐S6 fluorescence intensity increases considerably post intercalation, it can be used for the detection of Gram‐positive bacteria by the naked eye. COE‐S6 does not inhibit bacterial growth and is simple to use, making it a promising membrane‐specific fluorescent probe. Abstract : A fluorescent conjugated oligoelectrolyte with an elongated backbone can distinguish between Gram‐positive and Gram‐negative bacteria in a single step. This new technique enables in situ visualization of individual Gram‐types in complex polymicrobial biofilms and the detection of Gram‐positive bacteria by the naked eye by using a hand‐held UV lamp.